(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2026)
This article presents an extension experience in Santiago del Estero, aimed at strengthening community urban gardens through the social and solidarity economy and agroecology. Based on participatory action research (PAR) and popular education, the project articulated diagnostic assessment, training, and collective knowledge building with gardeners, technicians, and academics. Workshops on agroecological production, marketing, and food sovereignty were held in collaboration with INTA (National Institute of Statistics and Census), the Municipality, and the University. The results highlight the building of networks of trust and cooperation as a key pillar for strengthening agroecological production and solidarity-based exchange. Likewise, the need for tools to systematize experiences by promoters and municipal agents was evident. These demands open up new lines of collaborative work aimed at food sovereignty and the visibility of territorial experiences that are alternatives to the hegemonic model of food production and consumption.